2013
DOI: 10.4028/www.scientific.net/amr.868.287
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Geo-Grid to Enhence Stability of Tailings Dam

Abstract: The stability of tailing dams has recently become a hot issue on the engineering, and geo-synthetics curing processing applications are widely used. The influence of the tailings dam stability of geo-textile grid by calculating and analyzing with numerical simulation is studied. It reveals the mechanical behavior and the inherent law of the dam under different physical properties and different conditions of geo-grid. The force of reinforcement and the change law of ultimate load under different working conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Palmeira et al [10] presented a study on the use of nonwoven geotextiles in drainage and filtration systems of tailings dams and found the overall performance of the geotextiles tested under laboratory conditions was satisfactory. Zhang et al [11] found sinking displacement and collapse were reduced after adding geotextile grid and the stability of the tailings dam was effectively improved through numerical simulation analysis. Yang et al [12] pointed out that the application of geotextile tubes in the construction of tailings dam was beneficial for fine tailings disposal through a case study.…”
Section: Introductionmentioning
confidence: 99%
“…Palmeira et al [10] presented a study on the use of nonwoven geotextiles in drainage and filtration systems of tailings dams and found the overall performance of the geotextiles tested under laboratory conditions was satisfactory. Zhang et al [11] found sinking displacement and collapse were reduced after adding geotextile grid and the stability of the tailings dam was effectively improved through numerical simulation analysis. Yang et al [12] pointed out that the application of geotextile tubes in the construction of tailings dam was beneficial for fine tailings disposal through a case study.…”
Section: Introductionmentioning
confidence: 99%